IMPLEMENTASI PERDA KOTA SURABAYA NO. 9 TH 2014 TENTANG PENYEDIAAN RUANG BAGI PEDAGANG KAKI LIMA DI PUSAT PERBELANJAAN DAN PUSAT PERKANTORAN DI KOTA SURABAYA (Studi Kasus Di Kawasan Terminal Bratang Kecamatan Gubeng) - Saragih, Risman Taufiq (Universitas 17 Agustus 1945 Surabaya, 2016)
The structuring of policy and creation of internshipis so important to make the SurabayaCity to be clean, neat and comfortable. Formulating of government policy should be favormore than public interest, the conceptually providing of society is the eforts to increasingthe value and dignity of condition society is unable to escape from the poorness trap andunderdevelopment in other word empower is unable and to be an autonomous society. Thepurpose of the observation evaluation Perda Surabaya no. 9 Tahun about Provision up forinternship in Shopping and Office Center in Surabaya (Case Study In Terminal RegionBratang Gubeng ). The methods of observation is using descriptive methods with thequalitative approach and as a sample is information about the observation with dataaccumulation techniques are interviews, observation and documentation. The result ofobservation to showing if the Surabaya government in regulation of internship in Bratangterminal area in this case the entrance area Bratajaya Gubeng based on perda no 9 tahun2014 surabaya implemented in the form setup program, demolition and creation ofinternship in bratang terminal area is not match with the instruction. This casecan be seenfrom some of the factors that influence the success of the relocation policy evaluation asfollows : Relocation, this activity is to working when haven’t of land on location and theinternship is so many ; selter knock down, internship will be established selter like a tentand cart but just to activity in the evening. The cart is mobile everywhere ; Controlling , asa last resort if theinternship still stubbornly unwilling to follow the setup program Pemkot.This is a few opinion for Surabaya government to make a policy about structuring andempowerment of internship is expected better understand the issue of internship is fair .The other operating the internship and the Surabaya government can communicationbetween them through the agency internship community as a whole . Keyword : Implementation, Preparing room of Internship